User's Manual for the AAR-C2-2016 - Miller, Meagan; Vincent, Cynthia; Flynn, Robert J. (Université d'Ottawa | University of Ottawa, 2017)
We are pleased to present to practitioners, supervisors, quality assurance personnel, and researchers this User’s Manual for the 2016 version of the Second Canadian Adaptation of the Assessment and Action Record from Looking After Children (AAR-C2-2016; Flynn, Miller, Desjardins, Ghazal, & Legault, 2016). Our designation of the tool as the AAR-C2-2016 throughout the manual serves to distinguish it from its predecessors, the AAR-C2-2006 and the AAR-C2-2010. The manual is intended as a guide and reference tool for direct service, supervisory, and quality-assurance personnel. It will facilitate the analysis, interpretation, and presentation of OnLAC data at the individual, organizational, and provincial levels. The manual presupposes familiarity with the AAR-C2-2016 itself, gained through training in the Ontario Looking after Children curriculum as well as experience in administering or interpreting the instrument.
Keywords: child welfare; looking after children; children; child development; outcome monitoring